Histone Deacetylase Inhibitor Treatment Increases the Expression of the Plasma Membrane Ca2+ Pump PMCA4b and Inhibits the Migration of Melanoma Cells Independent of ERK - Hegedüs, Luca; Padányi, Rita; Molnár, Judit; Pászty, Katalin; Varga, Karolina; Kenessey, István; Sárközy, Eszter; Wolf, Matthias; Grusch, Michael; Hegyi, Zoltán; Homolya, László; Aigner, Clemens; et al. (Frontiers in Oncology, 2017)
Several new therapeutic options emerged recently to treat metastatic melanoma, however, the high frequency of intrinsic and acquired resistance among patients show a need for new therapeutic options. Previously, we identified the plasma membrane Ca2+ ATPase 4b (PMCA4b) as a metastasis suppressor in BRAF mutant melanomas and found that mutant BRAF inhibition increased the expression of the pump, which then inhibited the migratory and metastatic capability of the cells. Earlier it was also demonstrated that HDAC inhibitors up-regulated PMCA4b expression in gastric, colon and breast cancer cells. In this study we treated one BRAF wild type and two BRAF mutant melanoma cell lines with the histone deacetylase (HDAC) inhibitors SAHA and valproic acid either alone, or in combination with the BRAF inhibitor vemurafenib. We found that HDAC inhibitor treatment strongly increased the expression of PMCA4b in all cell lines irrespective of their BRAF mutational status, and this effect was independent of ERK activity. Furthermore, HDAC inhibition also enhanced the abundance of the housekeeping isoform PMCA1 more intensely in the BRAF mutant cells. Combination of the HDAC inhibitors with vemurafenib, however, did not have any additive effects on either PMCA isoform. We demonstrated that the HDAC inhibitor-induced increase in PMCA abundance was coupled to an enhanced [Ca2+]i clearance rate and also strongly inhibited both the random and directional movements of A375 cells. The primary role of PMCA4b in these characteristic changes was demonstrated by treatment with the PMCA4 specific inhibitor caloxin 1c2, which was able to restore the slower Ca2+ clearance rate and higher motility of the cells. While HDAC treatment inhibited cell motility it decreased only modestly the ratio of proliferative cells and cell viability. Our results show that in melanoma cells the expression of both PMCA4b and PMCA1 is under epigenetic control and elevation of PMCA4b expression either by HDAC inhibitor treatment or by the decreased activation of the BRAF-MEK-ERK pathway can inhibit the migratory capacity of the highly motile A375 cells.